A FEASIBILITY OF SAGORI ISLAND AS AN ENGLISH CAMP - ., Azhari; ., Roslina (PEOPLE: International Journal of Social Sciences, 2015)
This research aims to avoid a stagnant situation in terms of developing Sagori Island as an English Camp-based tourism village which is stand as a grand plan of the corporation between Universities Sembilanbelas November Kolaka and Kabupaten Bombana. To achieve the research objectives, this research was done under mix research method by using three different analysis techniques. First, Guidelines Analysis of Operational Area of Natural Tourism Object and Attraction of Directorate General of Forest Preservation and Natural Conservation 2003 was using for analyzing the potency of the Sagori Island. Second, SWOT analysis technique was using for determining the external and internal factors of Sagori Island. Third, participatory rural appraisal technique was using for analyzing the readiness of the Sugar’s resident. The result of the research showed that Sagori Island is feasible developed into the tourism village based English Camp by applied aggressive strategy and prioritize the participation of residents.